2021
DOI: 10.1017/pds.2021.62
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy and Digital Technologies: A Review of the Current Research Streams

Abstract: The interest in the Circular Economy (CE) has grown in recent years. Digital technologies (DTs) have demonstrated a potential synergy to achieve circular goals at the micro, meso, and macro-level. Although several studies in literature explore DTs and CE linkage, they have not been identified according to their primary research themes. This paper aims to identify the main research streams addressing CE and DTs. From a Systematic Literature Review and Content Analysis, we reviewed 40 articles and classified thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The M2 is associated with using a platform by various actors in the ecosystem, which facilitates and drives cooperation among actors (Konietzko, Bocken and Hultink, 2020;Ma et al, 2018;Vosman et al, 2021). The use of platforms and other digital technologies is also an essential point in the strengthening of CE (Trevisan et al, 2021a;Lobo et al, 2021). Moreover, M3 is related to lending production equipment to implement necessary processes (carton packages recycling and ecological tiles manufacture).…”
Section: Resultsmentioning
confidence: 99%
“…The M2 is associated with using a platform by various actors in the ecosystem, which facilitates and drives cooperation among actors (Konietzko, Bocken and Hultink, 2020;Ma et al, 2018;Vosman et al, 2021). The use of platforms and other digital technologies is also an essential point in the strengthening of CE (Trevisan et al, 2021a;Lobo et al, 2021). Moreover, M3 is related to lending production equipment to implement necessary processes (carton packages recycling and ecological tiles manufacture).…”
Section: Resultsmentioning
confidence: 99%
“…Riesener et al (2019) investigate how the transformation can occur and present recommendations for manufacturing companies on how digitalization can shift toward the circular economy principles. The transformation to the circular economy with the help of digital transformation occurs through three stages: micro-, meso-, and macro-levels (Trevisan et al, 2021). At the level of a single company, that is, micro-level, the circular economy is a business model innovation and processes related to monitoring, controlling, optimization, and automation (Porter and Heppelmann, 2014;Nasiri et al, 2017;Ingemarsdotter et al, 2019;Pieroni et al, 2019;Neligan et al, 2022).…”
Section: Digital Transformation-a Critical Factor For the Circular Ec...mentioning
confidence: 99%
“…This study contributes to one of the three research areas identified by Trevisan et al (2021) by focusing on the link between the Fourth Industrial Revolution and the circular economy. The importance of digital transformation in guiding the shift toward a circular economy is understood as the location problem of sectors characterized by HDI.…”
Section: Digital Transformation-a Critical Factor For the Circular Ec...mentioning
confidence: 99%
See 1 more Smart Citation
“…IoT and big data have been regarded as one of the promising tools to improve environmental sustainability and promote CE [49,50]. IoT has been applied for environmental monitoring in farming, domestic waste treatment, air quality, and urban CO 2 [51].…”
Section: Digital Technologies Implementation In the Water And Wastewater Sectormentioning
confidence: 99%